2014
DOI: 10.1016/j.ccr.2014.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Apo2L/TRAIL and the Death Receptor 5 Agonist Antibody AMG 655 Cooperate to Promote Receptor Clustering and Antitumor Activity

Abstract: Death receptor agonist therapies have exhibited limited clinical benefit to date. Investigations into why Apo2L/TRAIL and AMG 655 preclinical data were not predictive of clinical response revealed that coadministration of Apo2L/TRAIL with AMG 655 leads to increased antitumor activity in vitro and in vivo. The combination of Apo2L/TRAIL and AMG 655 results in enhanced signaling and can sensitize Apo2L/TRAIL-resistant cells. Structure determination of the Apo2L/TRAIL-DR5-AMG 655 ternary complex illustrates how h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
150
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(156 citation statements)
references
References 53 publications
6
150
0
Order By: Relevance
“…3A) (70), in the intracellular FasDD-FADD complex (Fig. 3B) (73), and for TRAF2 and TRAF6 oligomerization, consistent with a hexagonal lattice geometry (Fig.…”
Section: Tnfrsf Signaling May Be Described By a Uniform Hexagonal Modsupporting
confidence: 63%
See 3 more Smart Citations
“…3A) (70), in the intracellular FasDD-FADD complex (Fig. 3B) (73), and for TRAF2 and TRAF6 oligomerization, consistent with a hexagonal lattice geometry (Fig.…”
Section: Tnfrsf Signaling May Be Described By a Uniform Hexagonal Modsupporting
confidence: 63%
“…However, more recent studies have found that the combination of DR5-specific antibodies and hrTRAIL can synergize to kill cancer cells both in vitro (70,71) and in vivo (70). This combination therapy proved beneficial even in some previously TRAIL-resistant cancers.…”
Section: Tnfsf Ligands Are Essential For Tnfrsf Signaling-lessons Fromentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the encouraging results obtained at preclinical level, no convincing anticancer activity could be recorded in patients with cancer for any of the tested approaches (1)(2)(3)(4). This could be attributed to the different sensitivity of tumors to TRAIL on one hand and to the limited activity of targeting molecules, due to the short half-life of recombinant TRAIL and the monospecificity of the agonistic antibodies (Abs), on the other (1,5).…”
Section: Introductionmentioning
confidence: 99%